Decomposition of the International Chain of Deliveries of the Goods Containing Intellectual Property Items - A. G. Getman (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article substantiates the need to distinguish in the international chain of supply of goods as a specific product-a product containing an object of intellectual property, with its special structure, legal framework, regulatory mechanism, objects and subjects.The purpose: to identify in the field of international supply chains of goods specific product — a product containing an object of intellectual property, to highlight its main features, to propose a further direction of the theory.Materials and methods: the theoretical basis of the essence of the international supply chain, and the current customs legislation of the EAEU, national legislation in respect of goods containing intellectual property, the method of decomposition, system’s analysis method.The results: the multilevel structure of the international supply chain of goods containing intellectual property objects is developed with the help of decomposition method.Conclusion: the main directions of development of theoretical and methodological foundations in the logistics system — in terms of the international supply chain of a specific product — a product containing intellectual property, requires further research.